Impact of citizen participation on the tourism development of a region: case of Kabyle villages, Bejaia - Alili, Sonia; Guenadez, Zeineddine (Technium Social Sciences Journal, 2023)
Kabylia is a region of Algeria located on a mountainous part of the Mediterranean basin; it has a vernacular heritage with recognized socio-cultural, environmental and architectural qualities. Thanks to its assets, the development of tourism in the region will bring economic dynamism to the region. These villages are home to associations that used to exist under other names (Thajmaat, village committees). In this paper, we examine the real contribution of village associations to village tourism and the importance that citizen participation can have in a decentralized decision-making scheme.